19 Sleep-disordered breathing in heart failure patients requiring cardiac resynchronisation therapy: is there a link to poorer outcomes after device insertion. (7th October 2015) - Barrett, M; Cusack, R; Tobin, L; O'Rourke, A; O'Brien, A; Kiernan, T
Abstract : Rationale: We sought to ascertain the burden of undiagnosed sleep-disordered breathing (SDB) in high-risk heart failure patients, namely patients requiring cardiac resynchronisation therapy (CRT). Additionally, we looked for correlation between presence of SDB and change in cardiac function pre- and post-device. Methods: From a population of 40 patients with CRT devices implanted, a stable group of 18 were selected. Polysomnography was undertaken in each case. Apnoea-hypopnoea index (AHI), oxygen desaturation index (ODI), sleep efficiency, minimum oxygen saturation and snore index were calculated. Comparison was made to left ventricular function, left atrial dimension and mitral regurgitation severity pre- and post-implantation of CRT device. We also measured functional capacity of each patient using the International Physical Activity Questionnaire (IPAQ) tool and compared sleep profiled of those with a good functional capacity (>1000 MET minutes/week) against those with poor functional capacity. Data were analysed with simple descriptive statistics for baseline characteristics and comparisons made using Student t-test. Results: Our population had a high AHI (mean 14.2) and ODI (15.2) with poor sleep efficiency (mean 62%). 2 patients (11%) were classified as severe OSA (AHI > 30), and 11 (61%) had mild to moderate OSA. Patients were subdivided into those with improved cardiac function post-implant (n = 8) and those with unchanged or disimproved function (n = 10). Those patients who had an objective improvement in cardiac function by echocardiographic parameters were found to have a better overall sleep profile with a lower AHI (6.8 vs 16.05), snore index (32.6 vs 49.95) and higher sleep efficiency (63% vs 61%) and minimum nocturnal oxygen saturation (88% vs 83%). Patients with poor functional capacity as identified by were additionally found to have a higher snore index (48.7 vs 26.9) and poorer sleep efficiency (48.7 vs 71.8). Conclusions: There is a high prevalence of SDB in our cohort with a trend towards more severe sleep apnoea in non-responders to CRT. Failure to respond to appropriate device therapy in severe heart failure may be a red flag for clinicians, with identification and treatment of co-morbid sleep apnoea potentially having a role in optimising patient outcomes.